PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN FOOD AND BEVERAGE - Tri Kartika Pertiwi (Jurnal Manajemen dan Wirausaha, 2012)
The purpose of this study was to analyze financial performance as measured by Return on Assets (ROA) on firm value as measured by Tobin's Q as well as to analyze the Good Corporate Governance as a moderating variable. The research objects were food and beverage firms. The technique analysis was multiple linear regression analysis. The results showed that financial performance was influenced on the value of firms, while the Good Corporate Governance was not a moderating variable of the relationship between the financial performance and the firm value.